Analisis Sifat Mekanik pada Komposit dari Campuran Serat Limbah Rambut Manusia dan Sabut Kelapa - Miftahul Anwar; Deri Teguh Santoso; Ratna Dewi Anjani (Peneliti.net, 2021)
Currently, the use of materials in the engineering world is growing which encourages researchers from students, companies, to professors in various parts of the world to compete to find the best and environmentally friendly materials and can be recycled (biodegradable). One of them is to make composites from natural fibers as the main material, easy to obtain, high strength, and durable. In this study, the aim of this research is to influence the variation of fiber volume fraction and matrix on the mechanical properties of waste human hair fiber and coconut coir with an epoxy matrix. The method in making this composite uses the hand-lay-up method with a number of variations of 2 specimens each. The volume fraction variations that will be carried out in this study are 5% human hair: 5% coconut fiber: 90% epoxy matrix and 7.5% human hair: 7.5% coconut fiber: 85% epoxy matrix with the test used to test impact ASTM D256. The fiber from human hair itself is obtained from salon waste and the coconut coir itself is obtained from a seller of coconut ice which is dried and then the fiber is taken. Human hair fiber was chosen because it has protein ingredients that cannot be completely decomposed and coconut itself was chosen because it contains cellulose which is capable of having high tensile strength and tenacity. The results of the composite study of a mixture of human hair fiber and coconut fiber showed that the impact test had the best chance in energy and impact value at the volume fraction of 10%: 90%, respectively, 37.7 J and 0.72 J/mm2